Echinococcus oligarthrus in the subtropical region of Argentina: First integration of morphological and molecular analyses determines two distinct populations - Arrabal, Juan Pablo (2017)
Echinococcosis is a parasitic zoonosis that is considered as a neglected disease by the World Health Organization. The species Echinococcus oligarthrus is one of the causative agents of Neotropical echinococcosis, which is a poorly understood disease that requires a complex medical examination, may threaten human life, and is frequently associated with a low socioeconomic status. Morphological and genetic diversity in E. oligarthrus remains unknown. The aim of this work is to identify and characterize E. oligarthrus infections in sylvatic animals from the Upper Paraná Atlantic Forest in the province of Misiones, Argentina, by following an integrative approach that links morphological, genetic and ecological aspects. This study demonstrates, for the first time, one of the complete life cycles of E. oligarthrus in an important ecoregion. The Upper Paraná Atlantic Forest constitutes the largest remnant continuous forest of the Atlantic Forest, representing 7% of the world’s biodiversity. This is the first molecular determination of E. oligarthrus in Argentina. In addition, the agouti (Dasyprocta azarae), the ocelot (Leopardus pardalis) and the puma (Puma concolor) were identified as sylvatic hosts of Neotropical echinococcosis caused by E. oligarthrus. Mitochondrial and nuclear molecular marker analyses showed a high genetic diversity in E. oligarthrus. Moreover, the genetic distance found among E. oligarthrus isolates is higher than the one observed among Echinococcus granulosus genotypes, which clearly indicates that there are at least two different E. oligarthrus populations in Argentina. This study provides valuable information to understand the underlying conditions that favour the maintenance of E. oligarthrus in sylvatic cycles and to evaluate its zoonotic significance for devising preventive measures for human and animal wellbeing.